PARADIGMA INTEGRASI-INTERKONEKSI: Analisis Epistemologi Pemikiran Keislaman M. Amin Abdullah - ahmad izudin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2015)
This article is aimed to explore the dynamics of Islamic thought in the contemporary era, more specifically to explore the epistemological thinking of Amin Abdullah. Islamic thought in the contemporary era requires a renewal in the methodology, concepts and applications in the learning system so as not to suffer from a stagnation and deadlock of thought. On the basis of this assumption, this article will explain further regarding the view of Amin Abdullah, a Muslim thinker from Pati, Central Java, along with his broader horizons pertaining to the methodological approach of Islamic Studies. Therefore, this study is more specifically related to the paradigm of integration-interconnection in the methods of Islamic studies in which base the development of thinking was based on the Islamic epistemology which is open minded, inclusive and humanism.